Red Blood Cell Fatty Acid Patterns and Cognitive Functions in Adolescents: A Pooled Analyses with Two Cohort Study Data Sets - Ayala-Aldana, Nicolas; Pinar-Martí, Ariadna; Ruiz-Rivera, Marina; Lázaro, Iolanda; Sala-Vila, Aleix; Healy, Darren R.; Contreras-Rodriguez, Oren; Casanova, Jordi; Sola-Valls, Nuria; Vrijheid, Martine; Julvez, Jordi (Nutrients, 2025)
Objective: Fatty acids (FAs) play a pivotal role in brain development and cognitive functions during adolescence. We aimed to investigate the association of red blood cell (RBC) FA patterns and several high order neuropsychological functions in adolescents. Methods: The study followed a cross-sectional design. Principal component analysis was applied to 22 FA species previously measured in RBC membranes (exposure variable) to identify FA principal components (PCs) from two cohorts of adolescents in Catalonia, Spain (mean age = 14.53 years). Multiple linear regression was then used to examine associations between PC FAs and cognitive outcomes—working memory, fluid intelligence, and risky decision-making (gain and loss domains). Regression models were adjusted for child sex, age, body mass index, maternal education, and cohort enrollment. Results: Three FA PCs (eigenvalues > 2.0) were retained for the current study: a very-long chain FAs PC, a long-chain omega-6 FA PC and an omega-3 FA PC. The omega-3 FA PC showed a positive association with scores of fluid intelligence (β1 = 0.14, CI = 0.05, 0.24, p for trend = 0.003) and risky decision-making (loss domain) (β1 = 0.27, CI = 0.03, 0.52, p for trend = 0.030). The very-long chain FAs and long-chain omega-6 FAs patterns showed no significant associations with any cognitive outcome. The PC of omega-3 FA and fluid intelligence associations remained significant after multiple testing corrections. Conclusions: After applying an agnostic approach of multiple FAs in RBC, we found omega-3 FA patterns were positively associated with fluid intelligence among adolescents.